STUDI KOMPARATIF PENURUNAN TIANG BERDASARKAN DATA UJI PDA DAN BATAS PENURUNAN STANDAR ASTM D1143 - Puspa Ningrum; Muhmmad Yazid; Toni Hartono Bagio (LPPM Universitas Abdurrab, 2025)
The settlement characteristics of driven piles and bored piles vary depending on installation methods and subsurface conditions, necessitating accurate evaluation of foundation performance. This study aims to compare the settlement behavior of these two foundation types based on Pile Driving Analyzer (PDA) test results evaluated with reference to ASTM D1143 standards. Data were collected from 31 PDA test points across various projects in Riau Province, covering both driven and bored pile foundations. The analysis was conducted by comparing the maximum settlement values (DMX) obtained from PDA with the allowable maximum settlement (Sf) calculated according to ASTM D1143. The ratio between the actual data and the standard was assessed to determine settlement compliance. The results indicate that several driven and bored piles still exhibit settlement beyond the allowable limit, where the maximum settlement ratio DMX/Sf must be less than 1.00. Additionally, the presence of free-end type curves suggests excessive settlement in several samples. This study provides an important contribution to improving the accuracy of foundation capacity evaluation and serves as a basis for selecting and optimizing foundation design in sustainable infrastructure projects.